Metodologija reševanja ekonomsko-ekoloških problemov v lesnoindustrijskih podjetjih - Oblak, Leon (Zbornik gozdarstva in lesarstva, 1999)
Conservation and environmental protection are among the major world challengesin the next decade. To achieve the objectives of environment-friendly economic development, dynamic, flexible and profitable companies are needed, willing to deal with ecological issues. Since the wood industry contributes significantly to environmental pollution, it has become increasingly necessary to implement environment-friendly production, in addition to existing economic criteria. This is one of the very important strategic goals of the wood industry. There are problems however, since in ecological systems not only parameters defined by numerical variables are at play, but also subjective assessments and value judgments, which are difficultto define in absolute values. Finding optimal economic and ecologicalsolutions in the wood industry is an even more complex and demandingprocess, because mutually conflicting goals are usually involved. In this paper a methodology is developed for diagnosing the existing ecological state in wood industry systems, as well as finding the optimal solution with regard to their management, taking into consideration economic and ecological criteria.
Keywords: economics; ekonomija; environmental protection; lesna industrija; matematični modeli; onesnaževanje okolja; optimiranje; varstvo okolja